2022
DOI: 10.1109/jstars.2022.3157755
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Zhuhai-1 Hyperspectral Imagery With Sentinel-2 Multispectral Imagery to Improve High-Resolution Impervious Surface Area Mapping

Abstract: Mapping impervious surface area (ISA) in an accurate and timely manner is essential for a variety of fields and applications, such as urban heat islands, hydrology, waterlogging, and urban planning and management. However, the large and complex urban landscapes pose great challenges in retrieving ISA information. Spaceborne hyperspectral (HS) remote sensing imagery provides rich spectral information with short revisit cycles, making it an ideal data source for ISA extraction from complex urban scenes. Neverthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…A total of 21 features were calculated and fed to the cl sifier for ISA Mapping, including 3 spectral index features (NDVI, NDBI, MNDWI GLCM texture features, 10 land surface reflectance features, and 2 backscattering featur 3.2.1. Spectral Indices Feature Early studies indicated that combining spectral indices features is conductive to provement of accuracy in ISA mapping [38,39]. In this study, the following three spec indices features were calculated, including the Normalized Difference Vegetation Ind (NDVI), which can highlight vegetated land [40]; the Modified Normalized Differe Water Index (MNDWI), which has a good effect on distinguishing water bodies from la use/cover [41]; and the Normalized Difference Built-up Index (NDBI), which has a sign icant effect on the extraction of ISA [42].…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 21 features were calculated and fed to the cl sifier for ISA Mapping, including 3 spectral index features (NDVI, NDBI, MNDWI GLCM texture features, 10 land surface reflectance features, and 2 backscattering featur 3.2.1. Spectral Indices Feature Early studies indicated that combining spectral indices features is conductive to provement of accuracy in ISA mapping [38,39]. In this study, the following three spec indices features were calculated, including the Normalized Difference Vegetation Ind (NDVI), which can highlight vegetated land [40]; the Modified Normalized Differe Water Index (MNDWI), which has a good effect on distinguishing water bodies from la use/cover [41]; and the Normalized Difference Built-up Index (NDBI), which has a sign icant effect on the extraction of ISA [42].…”
Section: Feature Extractionmentioning
confidence: 99%
“…Early studies indicated that combining spectral indices features is conductive to improvement of accuracy in ISA mapping [38,39]. In this study, the following three spectral indices features were calculated, including the Normalized Difference Vegetation Index (NDVI), which can highlight vegetated land [40]; the Modified Normalized Difference Water Index (MNDWI), which has a good effect on distinguishing water bodies from land use/cover [41]; and the Normalized Difference Built-up Index (NDBI), which has a significant effect on the extraction of ISA [42].…”
Section: Spectral Indices Featurementioning
confidence: 99%
“…Hyperspectral image classification (HSIC) aims to assign a unique category identity to each element in the image, which is a key technology for the intelligent interpretation of the hyperspectral image (HSI) and has been widely used in many fields such as urban development planning [1,2], agricultural land use [3][4][5], military target detection [6,7] and medical pathological diagnosis [8,9]. However, the problems of low spatial resolution, high spectral dimensionality and lack of labelled samples in HSI pose great challenges to the classification task [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These subtle changes are rather identified by high-resolution hyperspectral imaging of the canopies where both changes in spectra and the texture appear [34]. Other researchers also found that hyperspectral cameras have great potential in detecting insect disturbances [35] but others highlighted that the best results are reaped when fusing spectral information from hyperspectral cameras with spatial information from satellite data [36]. Therefore, the aim of this study is to determine the best vegetation indices used for the recognition of defoliation as well as the type and position of the sensors.…”
Section: Introductionmentioning
confidence: 99%